2018
DOI: 10.1017/s095457941800038x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal stress, fetal programming, and mechanisms underlying later psychopathology—A global perspective

Abstract: There is clear evidence that the mother's stress, anxiety, or depression during pregnancy can alter the development of her fetus and her child, with an increased risk for later psychopathology. We are starting to understand some of the underlying mechanisms including the role of the placenta, gene-environment interactions, epigenetics, and specific systems including the hypothalamic-pituitary-adrenal axis and cytokines. In this review we also consider how these effects may be different, and potentially exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(131 citation statements)
references
References 141 publications
(175 reference statements)
3
123
0
5
Order By: Relevance
“…It has been demonstrated that PS can lead to an increase in DNA methylation at specific CpG sites within the 11β-HSD2 gene promoter in the placenta [67]. Furthermore, several studies have looked at alterations in the methylation of other genes, e.g., the glucocorticoid receptor (NR3C1) [68]. Other potential programming mechanism may include effects of PS on telomere biology [69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PS can lead to an increase in DNA methylation at specific CpG sites within the 11β-HSD2 gene promoter in the placenta [67]. Furthermore, several studies have looked at alterations in the methylation of other genes, e.g., the glucocorticoid receptor (NR3C1) [68]. Other potential programming mechanism may include effects of PS on telomere biology [69].…”
Section: Discussionmentioning
confidence: 99%
“…For at least two reasons, it is important to realize that fathering starts during pregnancy. First, the prenatal environment has far‐reaching consequences for child development (Glover, O'Donnell, O'Connor, & Fisher, ), and fathers can influence that environment positively (e.g., by quitting smoking) and negatively (e.g., by engaging in partner violence). Behaviors that protect the pregnant partner, such as ensuring that she gets sufficient rest and avoids pathogenic foods, protect the infant and benefit the baby’s development.…”
Section: A Biobehavioral Model Of Emergent Fatherhoodmentioning
confidence: 99%
“…In general, participants who did not provide data for this study had higher socio‐economic status than participants from whom data were analysed, but the differences were small and are unlikely to affect the validity of our results. This study only included characteristics of the living environment and basic maternal factors as exposure variables, but it is possible that unmeasured maternal factors like stress and exposure to violence could have an influence on children's gut microbiota in this population …”
Section: Commentmentioning
confidence: 99%